Representation of the social scopes of the female body. The case of young university students of the City of Mexico - Piñón, Maybel; Cerón, Cyntia (Última Década, 2020)
This article is a partial study which moves around the perceptions and social representations of the female body, in which these young students from two different universities have, one of a public scope: The Autonomous University of Mexico City, and the other from a private scope: The Intercontinental University. It is intended, from the qualitative method, to decipher how the feminine subjectivity operates in young people with the purpose of discovering, describing and understanding the ways in which they think, interpret and use their body daily. The work concludes with a presentation of the results of the first stage of this investigation, which is divided in three phases, where the main representations and scopes of relation with the body are located, which will be departure point for subsequent phases.